Bone Mineral Density, TBS, and Body Composition Indexes in Ukrainian Men with Parkinson’s Disease - Vladyslav Povoroznyuk; Maryna Bystrytska; Nataliia Grygorieva; Iryna Karaban; Nina Karasevich (Parkinson's Disease)
Introduction. Current research studies demonstrate the changes of bone mineral density (BMD) in subjects with Parkinson’s disease (PD); however, data about bone quality and body composition (BC) indexes are insufficient. The aim of the study was to assess the parameters of BMD, ВС, and trabecular bone score (TBS) in PD males. Materials and Methods. We performed a cross-sectional case-control research design and examined 76 males aged 50–77 years old, who were divided into two groups: first group including men without PD n=38 and the second group including subjects with PD n=38. Disease duration was at least 5 years; all PD participants were at levodopa therapy. BMD of lumbar spine, femoral neck, total femur, radius, and total body and TBS Ll−L4 were measured using the DXA method. Whole-body DXA measures were also used for the study of total, lean, and fat masses, skeletal muscle index (SMI), appendicular lean mass index (ALMI), and fat mass index (FMI). Results. Our study showed an increased incidence of osteoporosis and significantly lower total body BMD (respectively, 1.20 ± 0.13 and 1.26 ± 0.10 g/cm2, p=0.05), but not lumbar spine and femoral neck BMDs, and higher TBS value in PD men comparing to the control group (respectively, 1.33 ± 0.12 and 1.22 ± 0.18 un., p=0.005). Also, we established significantly decreased lower extremities BMD indexes, but not upper extremities, spine, and trunk BMDs in PD males. The femoral neck, proximal femur, and lower extremities BMD indexes in PD men were reliably lower at the side of predominance of clinical symptoms. Parameters of appendicular lean mass and ALMI in PD males were reliably higher, but fat mass values and FMI were lower compared to the control group in the absence of significant differences in lean mass values and SMI in weight-matched control. Conclusion. Due to low BMD values, changes in BC are present in PD males, and appropriate screening and preventive strategies should be instigated to maintain bone health in PD subjects.